Analisis Aturan Hukum Pengelolaan Taman Nasional Gunung Leuser (TNGL) Sebagai Warisan Dunia - Mhd. Nur Arrahman Nasution; Suhaidi Suhaidi; Syamsul Arifin; Jelly Leviza (USU LAW JOURNAL, 2019)
Abstract. Biological natural resources and their ecosystems are the most important part of natural resources comprising animal, vegetable or natural phenomena, either individually or jointly having the functions and benefits as elements of the environment, whose presence can not be replaced . In view of its irreplaceable nature and an important role for human life, the conservation of biological natural resources and their ecosystems is the absolute obligation of each generation. In fact, there are several issues and problems that occur in the area, one of which is the development and planning to conduct road construction that has been done before and after 2004, which resulted in WHC recommends TRHS area into natural heritage in danger (The List of World Heritage in Danger -WHD). Departure from the description of the background above, it can be formulated problems in research is, How the implementation of management in Taman Gunung Leuser National (TNGL) as World Heritage. In accordance with the research formulation, this study was conducted with normative juridical with the consideration that the starting point of analysis research on legislation regulating of Taman Gunung Leuser National, and sociological law enforcement. The result of the research is obtained the rule of law concerning the management of Gunung Leuser National Park as World Heritage still not running as it should because there is still activity activity which violate the regulation both nationally and internationally. These activities include illegal logging, illegal hunting, road clearing and forest fires resulting in disturbance and threats to the preservation of Taman Gunung Leuser National . The conditions of such areas resulted in TNGL and other National Parks being included in the UNESCO list of threatened (indengerlist). Keywords: rule of law, management of gunung leuser national park and world heritage.